Reinfection rate of hepatitis C in HIV-1 positive men who have sex with men: A systematic review and meta-analysis - Zhengwei Wan; Ping Sun; Emmanuel Enoch Dzakah; Liping Huang; Ping Shuai; Yuping Liu (Frontiers Media S.A., 2022)
PurposeA reduction of 80% in new Hepatitis C virus (HCV) infection is expected by 2030. However, high HCV reinfection rates have been reported among the high-risk population. This meta-analysis aimed to assess the HCV reinfection rate after successful treatment of HIV-1 coinfected MSM populations.MethodsBibliographic databases were searched and a random-effect model was utilized to calculate the pooled HCV reinfection rate. Sub-group and meta-regression were used to explore heterogeneity among selected studies. A funnel plot and Egger's regression test were performed to estimate the publication bias.ResultsSixteen studies with 9,017.2 person-years (PY) follow-up were included. The overall HCV reinfection rate following successful treatment among HIV-1-infected MSM was 5.27/100 PY (95% CI, 3.98, 6.96). Lower reinfection rates were observed in developed parts of Europe (5.28/100 PY; 95% CI, 3.73, 6.84) and North America (3.92/100 PY; 95% CI, 1.67, 6.17). Reinfection rates among people with HCV test intervals of fewer than 6 months (7.59/100 PY; 95% CI: 5.15, 10.03) were significantly higher than those with more than 6 months test interval (2.88/100 PY; 95% CI: 2.26, 3.50), with an adjusted RR of 1.86 (95% CI, 1.06, 3.13). The adjusted study factors explained 91.03% the of studies' heterogeneity.ConclusionHCV reinfection rate was high in successfully treated MSM who were coinfected with HIV-1. A shorter HCV test interval may help to explore more HCV reinfections. HCV reinfection rate studies from HIV-1 coinfected MSM in underdeveloped countries are urgently needed.Meta registrationPROSPERO: CRD42021285206, URL: https://www.crd.york.ac.uk/prospero/.